Developmental Trends and Research Hotspots in Bronchoscopy Anesthesia: A Bibliometric Study - Min, Keting; Wu, Yutong; Wang, Sheng; Yang, Hao; Deng, Huimin; Wei, Juan; Zhang, Xiaowei; Zhou, Huanping; Zhu, Wanli; Gu, Yang; Shi, Xuan; Lv, Xin (Frontiers in Medicine, 2022)
Background: This study aims to discuss the developmental trends and research hotspots in bronchoscopy anesthesia in the past decades. Methods: The original and review articles published from 1975 to June 2021 that related to bronchoscopy anesthesia were retrieved from Web of Science Core Collection (WoSCC). Three different scientometric tools (Citespace, VOSviewer, and Bibliometrix) were used for this comprehensive analysis. Results: There was a substantial increase in the research of bronchoscopy anesthesia in recent years. A total of 1270 publications were retrieved up to June 25, 2021. These publications were cited a total of 25504 times, with a mean of 20.08 citations per publication. The USA had the largest number of publications (27.6%) and the highest H-index (44). The sum of publications from China ranked the second (11.5%), with an H-index of 17. Keyword co-occurrence and references co-citation visual analysis showed that the use of sedatives such as dexmedetomidine in the process of bronchoscopy diagnosis and treatment was gradually increasing, indicating that bronchoscopy anesthesia was further progressing towards safety and comfort. Conclusion: Based on bibliometric analysis of the publications over the past years, a comprehensive analysis indicated that the research of bronchoscopy anesthesia is in a period of rapid development and demonstrated the improvement of medical instruments and surgical options contributed significantly to the field of bronchoscopy anesthesia. The data would provide future directions for clinicians and researchers relative to the bronchoscopy anesthesia.